Eu sou uma pessoa normal, entendeu: gênero, corpos e subjetividades na pornografia. - Crestani, Aline MIchelli (2019)
Discussing pornography is touching the interdict, and even though it is present in most different times and societies, the limits and representations that define it have undergone transformations throughout history; pornography is, therefore, a social phenomenon. Through this research, I attempt to understand the construction of the career of pornographic film actresses in Brazil, analyzing the constitution of the multiple subjects that emerge in their narratives. Making use of Oral History as a methodological tool, for the development of this research, I carried out five interviews with women who recognize and present themselves as porn actresses. In addition, I analyzed materials published by them on their social networks (Instagram and Twitter), given the fact that I understand these materials as self-writings, carefully composed and through which autobiographical narratives are constructed. From a Foucauldian perspective, through which subjects constitute themselves through their discourse at the center of power relations, spoken words are enough; thus, in this perspective, I concentrated my readings and analyses of such narratives. By overlapping their stories, I was able to understand the meaning that the profession inputs to the construction of their identities, considering the issues involving discussions about gender and sexuality, and thus, to deconstruct myths and social judgment.